PENGARUH KONSENTRASI DAN FREKUENSI APLIKASI ETEPHON TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MENTIMUN (Cucumis sativus L.) - Cici Octavia Sidauruk; Jasmani Ginting; Justin Napitupulu Napitupulu (Universitas Sumatera Utara, 2013)
ABSTRACTThe effect of Concentration and Frequency of Etephon Aplication on Growth and Production ofcucumber (Cucumis sativus L.). Cucumber in Indonesia is popular and likely vegetable for all ofsociety. Cucumber productivity (ton/ha) in Indonesia from 2007 to 2011 were decrease from 81.2 to527.1 this was due to less intensive and efficiency in cucumber culture one of the alternative that couldbe done was application etephon of plant growth regulator. The aim of this research was to know theeffects of concentration and frequency of etephon application on growth and production of cucumber,this study was done in faculty of agriculture net house medan (± 25 in above sea level) from Januari –maret 2013. The design used was Randomised Block Design with 2 factors, etephon concentration (0.150, 300 dan 450 ppm) and the frequency of application (1x, 2x and 3x times). The parameterscolected were plant length, number of leaves formed, number of lived leaves, number of femaleflowers, number of female flowers aborted, number of male flowers, ratio of flowers, number of fruitper plant and total weight perplant. From the research, concentration affect significantly on plantlength (4-8 weeks after planting), number of female flowers (39 and 51 days after planting), number offemale flowers aborted (42 and 60 days after planting), number all of male flowers, ratio of flowers (48days after planting). Frequency aplication of etephon affect significantly plant length (6-7 weeks afterplanting). Interaction affect significantly on flowers ratio (48 days after planting ).Keywords : cucumber, concentration , and frequency Etephon.